Esenbeckia (Esenbeckia) auribrunnea n. sp. (Diptera: Tabanidae) from the Amazon, with a key to the Neotropical species of the subgenus - Gualdrón-Díaz, Juliette Cristina; de Sousa Gorayeb, Inocêncio (Zootaxa, 2020)
We describe a new species of horse fly, Esenbeckia (Esenbeckia) auribrunnea n. sp. from Rondônia (Brazil) and Vaupés (Colombia), including diagnoses, distributional records, measurements of body and head, photographs in dorsal, lateral and ventral views, and illustrations of genitalia of a female paratype. In addition, we presented an updated and modified key to species in the subgenus described in the last 23 years based on Wilkerson & Fairchild’s (1983) key: E. hirsutipalpus Wilkerson & Fairchild, from Mexico, and E. gracilipalpis Chaney & Hall, from Bolivia; E. griseipleura Chainey & Hall, from Bolivia; E. peruviana Burger, from Peru; and E. rafaeli Limeira-de-Oliveira, from Maranhão state, Brazil. The species E. diaphana (Schiner) from Colombia, and E. distinguenda Lutz & Castro from Rio de Janeiro, Brazil, are not included with justifications.